Gold Nanoparticles as a Platform for Delivery of Immunogenic Peptides to THP-1 Derived Macrophages: Insights into Nanotoxicity - Eduardo Zúñiga; Braulio Contreras-Trigo; Jorge Buchert; Fabián Sáez-Ahumada; Leonardo Hernández; Víctor Fica-León; Estefania Nova-Lamperti; Bostjan Kobe; Fanny Guzmán; Víctor Diaz-García; Enrique Guzmán-Gutiérrez; Patricio Oyarzún (Vaccines)
Background: Peptide-based nanovaccines have emerged as a promising strategy for combating infectious diseases, as they overcome the low immunogenicity that is inherent to short epitope-containing synthetic peptides. Gold nanoparticles (AuNPs) present several advantages as peptide nanocarriers, but a deeper understanding of the design criteria is paramount to accelerate the development of peptide-AuNPs nanoconjugates (p-AuNPs). Methods: Herein, we synthesized and characterized p-AuNPs of 23 nm (p-Au23) and 68 nm (p-Au68) with varying levels of peptide surface coverage and different peptide designs, investigating their effect on the cell viability (cell death and mitochondrial activity), cellular uptake, and cathepsin B activity in THP-1 macrophages. Results: p-Au23 proved no negative effect in the cell viability and high levels of nanoconjugate uptake, but p-Au68 induced strong toxicity to the cell line. The peptide sequences were successfully designed with spacer regions and a cell-penetrating peptide (pTAT) that enhanced cellular uptake and cathepsin B activity for p-Au23, while pTAT induced severe effects in the THP-1 viability (~40–60% cell death). Conclusions: These findings provide valuable insight into the design criteria of AuNPs and immunogenic peptides, along with nanotoxicity effects associated with AuNP size and surface charge in human monocyte-derived macrophages.